The influence of profitability and financial leverage on company value in the registered telecomunications sub-sectors on BEI 2017-2022 - Togar Naibaho; Veranda Panjaitan; Syah Paradiba Sirait (International Journal of Applied Finance and Business Studies, 2023)
This study aims to determine the effect of Profitability and Financial Leverage on Firm Value in Telecommunications sub sector companies. The data for this research were obtained from annual report documents of companies in the telecommunications sub sector on the official website of the Indonesia Stock Exchange from 2017-2022. The results showed that the independent variable consisting of Profitability and Financial Leverage on the dependent variable, namely Firm Value with a significance value of Profitability of 0,001 < 0,05. Then Financial Leverage is 0,011 < 0,05. These results can be concluded that the variable Profitability have significant effect on Firm Value in telecommunications sub sector companies, while Financial Leverage have no significant effect on Firm Value in telecommunications sub sector companies.